Effect of light transmitted through fiber post on composite polymerization - Varjus, Roope (My University, 2025)
Purpose: The aim of this study was to investigate how well core build-up composite polymerizes when light is transmitted through a fiber post. Materials and Methods: Two different composites were studied: light-cure flowable short fiber- reinforced composite (SFRC) everX Flow (GC) and dual-cure composite Gradia Core (GC). Three different fiber-reinforced composite (FRC) posts were used. Two of them were prefabricated FRC posts, MI Core Fiber Post (GC) and Snowpost (Abrasive Technology), with a cross-linked polymer matrix. The third was individually formed FRC post with semi-interpenetrating polymer network (semi-IPN) polymer matrix, everStick Post (GC). A 4 mm thick polyvinylsiloxane putty disc was prepared with a 1.5 mm diameter hole to hold the post in place during curing. A light-protected cylinder was filled with composite and the putty disc with the post was placed on the cylinder. Light was transmitted to cure the composite through the post for 20 or 40 s. Immediately after light- curing, the posts were gently scraped clean of non-polymerized composite and wiped with ethyl alcohol. The posts with the attached, solidified composite, were then weighed and visually analyzed for determining quantity of polymerized composite on post surface. In addition, the diameters of the posts were measured at six different depths (4, 8, 12, 16, 20, and 24 mm) from the cervical end. Results: The composites everX Flow (GC) and Gradia Core (GC) did not differ statistically when looking at the quantity of attached composite to different posts (ANOVA, p> 0.1). The MI Core Fiber Post group and everStick Post (GC) group showed significantly higher quantity of attached composite on post surface compared to the Snowpost group (p< 0.001), suggesting better transmission and scattering of curing light. Conclusion: The results showed that composite resins may be adequately polymerized by curing light through the post only. This suggests that, in some occasions, light-curing composites could be used for luting fiber posts to the root canal.
Keywords: Flowable short fiber-reinforced composite, Fiber-reinforced composite post, Individually formed fiber-reinforced composite post